PATH ANALYSIS COMMUNICATION MODEL OF COOPERATION ORGANIZATION IN THE DEVELOPMENT AGRICULTURAL MECHANIZATION (VILLAGE UNIT COOPERATIVE/VUC RICE MILLING UTILIZATION CASE IN KARAWANG AND CIANJUR DISTRICT WEST JAVA PROVINCE) - Parlaungan Adil Rangkuti; Amiruddin Saleh (Business and Entrepreneurial Review, 2011)
The objectives of this research were (1) to explain VUC organization communication factors whichare the key in improving the VUC performance, (2) to explain VUC organization communicationfactors that become the key in developing the VUC capacity, and (3) to formulate defined strategyin improving the VUC quality service as the agricultural economic organization for agriculturalmechanization development. Active category of VUC sample as analysis unit was determinedby each of five VUC samples at Karawang and Cianjur District. From each VUC sample, thirtyrespondents that use rice milling of VUC, were taken. This research was designed using surveymethod with multi analysis approaches, they were: descriptive analysis and path analysis usingSEM (Structural Equation Model) analysis with LISREL analysis support. The primer andsecondary data were collected from December 2009 to March 2010. The result of this researchshowed that (1) according to the similarity test model referring to the goodness of fit criteriafrom SEM analysis showed that VUC organization communication model is good, (2) level ofperformance, capacity, and quality of VUC service at Karawang and Cianjur District classifiedas low,(3) determinant factors which have real influence on the low performance and capacityof VUC are low quality of information, inconvenient organization communication environment,and low intensity of public organization communication, (4) determinant factors which have realinfluence on the low quality of VUC service are low quality of VUC personnel characteristicand weak VUC organization communication process, and (5) improvement strategy of VUCquality service should be done by developing VUC organization communication model throughagricultural information system development in the centers of agriculture production in eachrural area towards modern agriculture.